Avaliação da anastomose colo-cólica com e sem preparo intestinal : estudo experimental em cães - Figueiredo, Wellington Ribeiro (2012)
The objective of this study was to evaluate the efficacy of colo-colonic anastomosis in dogs with and without preoperative bowel preparation. The experiment included 42 healthy female mongrel dogs (Canis familiaris) weighing 8.4-16.9 Kg, supplied by the municipal dog pound of Teresina, Piauí. The animals were distributed at random in two groups of 21 animals each: Group I (control) = submitted to bowel preparation with rectal administration of 12% glycerin solution one day before the procedure, and Group II (study) = without previous bowel preparation. All animals were submitted to laparotomy with sectioning of the descending colon and primary anastomosis using polypropylene thread under the peri and postoperative supervision of a veterinary physician. The animals were allowed access ad libitum to water and standard feed following the first evacuation. On the 21st postoperative day (POD 21), the dogs were euthanized with ketamine i.v. followed by 20% potassium chloride i.v., and a second laparotomy was performed through the same incision in order to evaluate the anstomosis. In addition, the abdominal cavity was evaluated for adhesions and the burst pressure of the anastomosis was tested. The unpaired samples were compared with Studentʼs t test for parametric data and with the Mann-Whitney test for non-parametric data. One animal in each group (4.5%) died. The death in Group I (control) occurred on POD 7 due to anastomotic dehiscence. The death in Group II (study) occurred on POD 10 due to deep incisional infection at the surgical site and complete dehiscence of the abdominal wall. The groups did not differ significantly with regard to adhesion grade or anastomotic burst pressure (one specimen burst in each group) (p>0.05). In conclusion, the level of safety and efficacy was the same for colo-colonic anastomosis with and without previous bowel preparation.